Concept brand for experimental theatre - Achilleos, Andreas (Τμήμα Πολυμέσων και Γραφικών Τεχνών, Σχολή Εφαρμοσμένων Τεχνών και Επικοινωνίας, Cyprus University of Technology, 2011)
The main title of the thesis is “Concept Brand for Experimental Theatre”. Field of study is typographic design. The thesis is consisted of two parts Theory and Design. Theory part examines elements of typographic style, and theatre on both Futurist and Dada movements, while design part methodology examines construction and deconstruction of typographic design by using variant techniques, conventional and / or new media. Futurism and Dada movements were considered during research about typographic design and theatre movements in art and design which they were happening simultaneously. Those two movements had the most controversial and experimental format in typography, art, and design widely. Association completed on how theatre experimentation and actions on it, affected the elements of typographic design and vice-versa. On the whole, research and experimentation resulted to design a mini concept - poster booklet, which promotes the poster design and performances of experimental theatre.
Keywords: Theatre; Θέατρο